Uncovering the WHY of Consumer Behavior - From Neuroscience to Implementation - Enrique Strelow; Christian Scheier (Marketing Review St.Gallen, 2018)
Neuroscience has identified the core drivers of consumer behavior. The challenge for marketing is to make these insights actionable in day to day marketing. Using a FMCG case study, this paper introduces a systematic approach that leverages neuroscience insights to uncover the why of brand choice, helps to evaluate communication at touchpoints and maximize marketing effectiveness in driving fit to brand and sales.
Keywords: 650